Quality of life of women with polycystic ovary syndrome of reproductive age - Mlinar, Suzana (Vojnosanitetski pregled, 2026)
Background/Aim. Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, and it affects their physical and mental health and their quality of life (QoL). The aim of this study was to assess the QoL of women with PCOS of reproductive age. Methods. The study included 100 women, aged 18 years or above, diagnosed with PCOS. The Short Form Health Survey-36 (SF-36) was used as the research instrument. Mann-Whitney U test, Kruskal-Wallis test, and Spearman’s rank correlation coefficient were used to examine possible differences in QoL within the variables studied. Results. Women with PCOS living in rural areas had a significantly higher mean score in the vitality domain. A statistically significant, strongly positive correlation with the total QoL score was found for the Mental Component Summary (MCS) (p < 0.001) and Physical Component Summary (PCS) (p < 0.001) subscales. A statistically significant but weak negative correlation was found between self-rated health and the PCS (p = 0.021), the MCS (p = 0.004) and the total QoL score (p = 0.002), and age with the PCS (p = 0.023) and the total QoL score (p = 0.032). Conclusion. Women with PCOS in rural areas were more vital and had better QoL. Lower self-esteem regarding health is associated with poorer QoL, especially in the psychological domain. In women with manifest PCOS, early diagnosis and appropriate education can help alleviate certain symptoms and prevent serious complications.
Keywords: health; polycystic ovary syndrome; quality of life; surveys and questionnaires; women.